The origin of the Haidahs of the Queen Charlotte Islands [electronic resource] - Campbell, John, 1840-1904; Royal Society of Canada. ([S.l. : s.n., 1897)
From: Transactions of the Royal Society of Canada, Section II, 1897. Caption title. Electronic reproduction. Mode of access: Internet. 44